Ektraksi Ciri Citra Tcrmogram Payudara Bcrbasis Dimcnsi Fraktal - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The primary purpose of infrared thermography is the locating of thermal diffirences and anomalies. Irifrared thermography can detect numerous conditions in which an anomaly is characterized by an increase or decrease in surface temperature. In this research, we specifically applied calculation offractal dimension method to a total of 20 thermograms of normal breasts as well as of those in advanced breast cancer. In addition standard image pre-processing were also used to enhance the df!tection capabilitity. Several methods in image processing which are pre-processi1'Jg with canny edge detection, thresholding, calculation offractal dimension use box-counting and Hausdorff dimension. The results of this research are shown that Ilausdorff dimension in the normal thermograms have range value 0,4 - 0,95 smaller than .the advanced thermograms which have value more than 1,26. Finally this results show that the diffirence of fractal dimension can be used to distinguish between normal and advanced thermograms. Keywords: canny edge detection, thresholding,fractal dimension, box-counting, Hausdorff